PERILAKU BERUANG MADU DI KAWASAN WISATA PENDIDIKAN LINGKUNGAN HIDUP KOTA BALIKPAPAN - Sri Ngabekti (Universitas Sebelas Maret, 2014)
Sun bear (Helarctos malayanus) is one of the fauna in East Kalimantan, included to protected biodiversity. Since 2002 sun bear used to be the mascot of Balikpapan City. To save the population of sun bear, there isKawasan Wisata Pendidikan Lingkungan Hidup (KWPLH) in which there are five sun bears in the enclosure area of 1.3 hectares. Outside the enclosure, there is a boardwalk along 400 meters which provided for visitors to see and observe the sun bears and their behavior directly. This study aims to examine the behavior of sun bears at KWPLH Balikpapan City. Used method is the method of survey, interviews, and document analysis. The results showed there were at least four observable behavior which are feeding behavior, social, activities, and communication. Eating behavior that were seen aretheir way to eat and the type of food. There are different relationship in social behavior such as nice fellow, polite, cranky, or irritable. Sun bear’s active time is during the afternoon (diurnal). To communicate between sun bears, it can be done through sound, smell, and various facial expressions. The conclusion in this study is sun bear’s behavior can be observed well if it maintained in an extensive enclosure and managed according to the condition of natural habitats. Keywords : educational tour, sun bear, behavior